CONTENT ANALYSIS OF COMMENTS ON SERVICE, SATISFACTION AND EXPERIENCES OF "ALBERGO DIFFUSO" VISITORS: TRIPADVISOR CASE - Aksöz, Emre Ozan; Ürgün, Gamze Kayan (Economic Outlook, 2023)
The Albergo Diffuso model is a new model of sustainable development, based in Italy, which aims to utilize both tangible and intangible local resources. Today, this model is becoming increasingly popular in the tourism sector, where it is used to support local communities, preserve cultural heritage, enhance the tourist experience and promote sustainable tourism. In this direction, the aim of this study is to determine the touristic experiences of tourists staying in Albergo Diffuso hotels through their reviews on TripAdvisor digital travel platform and the factors that may affect their experiences. The study will analyze 100 reviews for two Albergo Diffuso hotels in Italy. The findings of this research showed that these contents can be categorized under four factors. These factors are listed as "hotel overall", "staff", "hotel room" and "food and beverage" according to their importance in tourists' hotel stay experiences.
Keywords: Albergo Diffuso; sustainable tourism; hotel reviews